Analysis of changes of the rats’ peripheral blood with prolonged exposure to various dose multicomponent means - Adamovich, Anna V.; Rimzha, Elena A.; Sherstyuk, Galina V.; Dudchyk, Natallia V. (Experimental Biology and Biotechnology, 2017)
The article presents results of studying potential toxicity of the original multicomponent composition for prevention and correction of tobacco use effects. At one of the toxicological studies stages, the effect of multiple intake of this composition on the state of peripheral blood of laboratory animals (rats) was evaluated. The results of 30- and 60day experiments revealed a few changes in individual hematological parameters, which depended on the admission duration and the dose of the drug. The character of the changes suggests that they are an adaptive response of the body to the long-term influence of a complex of xenobiotics with a multiple effects. In general, assessment of the animals’ hematologic status on the both experimental dates, the depth and temporality of the revealed changes indicate the absence of a pronounced toxic effect of the composition at its long-term use.